Evaluación de la cartera de crédito y el riesgo crediticio de la Coac. Fernando Daquilema Ltda. Periodo 2016-2017 - Unach (2019)
This reaearch is intended to analize the credit portfolio of the COAC Fernando Daquilema Ltda, period 2016-2017, it is structured of the following way; The first phase is about to the reference framework in which the project is based; The approach of the problem, justification and objectives. The second phase refers to the state of the art, known as the theoretical framework, is composed of the generalities of the company, as well as for each variable of the research. The first variable is the credit portfolio, where an assessment of the situation of the Coac portfolio was made Fernando Daquilema by means of financial indicators and vertical and horizontal analysis of the financial statements, The other variable was the credit risk that COAC had in the years 2016 – 2017 and the degree of influence in the recovery in these credits. Within the methodology, specific procedures are planned to determine the findings, which are supported by the surveys, while in the analysis and interpretation of our field research is carried and in turn, our hypothesis was verified. Therefore, from this study we can concluded our conclusions and recommendations to the main officials in charge in the area of credits of COAC. Fernando Daquilema Ltda.